The (in) equivalence in the translation of the legal texts of succession from Arabic to Spanish - Mohammed, Salam Naji; Jasim, Reyadh Mahdi (Al-Adab Journal, 2022)
Legal translation is characterized by complexity, especially when translating from two very different legal systems such as Iraqi and Spanish, where the divergence of culture, language and especially legal systems play a very important role in the translation and makes the translation process even more difficult for the translator. In this research we will address the case of (in) equivalence in the translation of succession documents from Arabic to Spanish, we will cite the classifications of said equivalences according to the most prominent linguists, speaking in detail of each type, and also of their role in legal language, Then we analyze some Arab legal documents, more precisely from Iraq, highlighting the type of equivalence in each term and in case it does not have one, highlighting the best translation procedure. We will also address sources of Iraqi law that are borrowed from islam, and that, in turn, further complicates the translation procedure.